Democracy and Elections in Guatemala - Roos, Stefanie Ricarda (Tufts Archival Research Center, 2005)
Volume 21, Issue 1. Winter/Spring Guatemala has entered into a new phase in its political development as it moves away from a history of political oppression and violence.